Directive Antenna for Ultrawideband Medical Imaging Systems - Amin M. Abbosh (International Journal of Antennas and Propagation)
A compact and directive ultrawideband antenna is presented in this paper. The antenna is in the form of an antipodal tapered slot with resistive layers to improve its directivity and to reduce its backward radiation. The antenna operates over the frequency band from 3.1 GHz to more than 10.6 GHz. It features a directive radiation with a peak gain which is between 4 dBi and 11 dBi in the specified band. The time domain performance of the antenna shows negligible distortion. This makes it suitable for the imaging systems which require a very short pulse for transmission/reception. The effect of the multilayer human body on the performance of the antenna is also studied. The breast model is used for this purpose. It is shown that the antenna has more than 90% fidelity factor when it works in free space, whereas the fidelity factor decreases as the signal propagates inside the human body. However, even inside the human body, the fidelity factor is still larger than 70% revealing the possibility of using the proposed antenna in biomedical imaging systems.